Crystal lattice disorder and characteristic features of the low-temperature thermal properties of higher borides. Issue 7 (29th January 2020) - Novikov, V. V.; Matovnikov, A. V.; Mitroshenkov, N. V.; Shevelkov, A. V.; Bud'ko, S. L.
Abstract : Heat capacity C P ( T ) and lattice parameters a ( T ), b ( T ) and c ( T ) of LuB44 Si3.5 borosilicide are experimentally studied as a function of temperature in the range of 2–300 K. Abstract : Heat capacity C P ( T ) and lattice parameters a ( T ), b ( T ) and c ( T ) of LuB44 Si3.5 borosilicide are experimentally studied as a function of temperature in the range of 2–300 K. The results are compared with those of pseudo-isostructural LuB50 boride. At the lowest temperatures, it is shown that the C P ( T ) dependence of borosilicide changes linearly with temperature. This is attributed to the effect of glass-like behaviour of the heat capacity due to the disorder in the sublattice of non-metals. The presence of defects in the B–Si sublattice and the irregular form of the cages in the B–Si matrix, which are occupied by Lu 3+ ions, lead to the formation of two-level systems (TLS) in the Lu 3+ subsystem. The TLS make a characteristic bell-like low-temperature contribution to the heat capacity of borosilicide. We show that there is a wide temperature range (5–150 K) of negative thermal expansion of borosilicide, which is attributed to the influence of quasi-independent vibrations of Lu 3+ ions in the cages of the borosilicide crystal structure.